Efficacy of Transcranial Magnetic Stimulation for Reducing Suicidal Ideation in Depression: A Meta-Analysis - Cui, Yanan; Fang, Haijian; Bao, Cui; Geng, Wanyue; Yu, Fengqiong; Li, Xiaoming (Frontiers in Psychiatry, 2022)
Objectives This study aimed to systematically review the efficacy of transcranial magnetic stimulation treatment in reducing suicidal ideation in depression. Methods PubMed, Web of Science, CBMdisc, WanFang, Chongqing VIP, and CNKI databases were electronically searched for randomized controlled trials of transcranial magnetic stimulation (TMS) intervention in the management of suicidal ideation from inception to February 24, 2021. Two reviewers independently screened studies, extracted data, and assessed the quality of included studies. Meta-analysis was then performed using STATA 15.1 software. Results A total of eight articles involving 566 patients were included. The meta-analysis results showed that the suicidal ideation scores of the group who received TMS treatment were significantly lower [standardized mean difference (SMD) = −0.415, 95% confidence interval (CI): −0.741 to −0.090, P = 0.012] than those of the control group. Subgroup analysis showed that age, TMS pattern, frequency of intervention, and stimulation threshold altered the TMS efficacy. Conclusions Evidence showed that TMS achieved superior results in reducing suicidal ideation. Because of the limited quality and quantity of the included studies, more high-quality studies are required to verify the conclusions. Systematic Review Registration https://inplasy.com/, identifier: INPLASY202180065.